National College Entrance Exam in China Perspectives on Education Quality and Equity - Zhang, Yu (SpringerBriefs in Education, 2016)
This book focuses on the National College Entrance Exam (NCEE), an important measurement of education quality in China, from both education economics and education policy perspectives. It provides a better understanding and stimulates more sophisticated evaluations of NCEE-related policies in China from the perspectives of education equity, the effectiveness of education input, and education quality. This book reports inspiring findings based on high-quality individual level data, innovative measurement design, and various appropriate identification strategies. The most import conclusion is that both education equity and quality can be achieved using well-designed policies based on solid empirical evidence. This is likely the first book published in English to discuss the NCEE so extensively from multiple perspectives using concrete evidence.